Похідні балансові звіти як інструмент стратегічного обліку - Криштопа, І.І. (Культура народов Причерноморья, 2013)
За результатами проведеного дослідження в статті висвітлено сутність похідних
балансових звітів та проаналізовано зміст найпоширеніших їх видів. Також, автором виокремлено
проблемні аспекти у класичному алгоритмі побудови стратегічного похідного балансового звіту та
запропоновано напрямки їх вирішення. По результатам проведенного исследования в статье отражена сущность производных
балансовых отчетов и проанализировано содержание распространенных их видов. Также, автором
выделены проблемные аспекты в классическом алгоритме построения стратегического производного
балансового отчета и предложены направления их решения. According to the results of the study, the article deals with the definition of the essence of the
derivative balance sheets and investigates their most common types. Also, next problematic aspects of the classic
algorithm of building of strategic derivative balance sheet have been highlighted by the author:
- neglecting the influence of intellectual capital on the performance of the enterprise;
- impossibility of the appraisal of influence of chosen strategies on the development of the enterprise in order to
choose the best way of its functioning.
In order to solve the first problem the author proposed to use corrective entries for the inclusion of the
information about structural, human capital and client capital into the strategic derivative balance sheet.
In order to solve the second problem, the author recommended to allocate the following steps into traditional
algorithm of building of the strategic derivative balance sheet:
- appraisal of the current selected indicators of the enterprise;
- appraisal of the selected indicators of the enterprise after implementation of hypothetical variant of the
strategy into the practice.
-Implementation of these recommendations into the practice of building of the strategic derivative balance
sheet will ensure the effectiveness of management decisions regarding the selection and implementation of
enterprise development strategies.